2018
DOI: 10.14740/jocmr3364w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Cardio-Ankle Vascular Index as a Cardiovascular Risk Factor in Elderly Patients With Type 2 Diabetes Mellitus

Abstract: BackgroundThe cardio-ankle vascular index (CAVI) is a novel physiological marker of atherosclerosis that reflects systemic arterial stiffness. The aim of this study was to clarify the clinical significance of CAVI as a risk factor for cardiovascular diseases (CVDs) in elderly patients with type 2 diabetes mellitus.MethodsThis cross-sectional study enrolled 216 elderly (≥ 65 years) outpatients with type 2 diabetes mellitus who were undergoing antidiabetic treatment (96 males and 120 females; mean age, 75 ± 7 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
3
9
0
Order By: Relevance
“…Basic studies have reported that AGEs or RAGE can induce inflammation, oxidative stress, and calcification in vascular cells, such as endothelial or smooth muscle cells [ 32 - 34 ]. Clinical studies have also indicated a significant association between skin AF and physiological markers of arterial function, including CAVI [ 35 - 37 ]. On the contrary, some researchers have shown the importance of arterial function in the pathogenesis of CHF [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Basic studies have reported that AGEs or RAGE can induce inflammation, oxidative stress, and calcification in vascular cells, such as endothelial or smooth muscle cells [ 32 - 34 ]. Clinical studies have also indicated a significant association between skin AF and physiological markers of arterial function, including CAVI [ 35 - 37 ]. On the contrary, some researchers have shown the importance of arterial function in the pathogenesis of CHF [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…CAVI provides a novel marker of systemic arterial stiffness that is independently associated with blood pressure [ 12 ]. A number of studies have reported the clinical usefulness of CAVI as a cardiovascular risk factor [ 34 - 36 ]. In the present study, CAVI > 9 was one of the strongest predictors of MACE of all the explanatory variables.…”
Section: Discussionmentioning
confidence: 99%
“…The CAVI before RARP was used to evaluate the severity of atherosclerosis . The CAVI was measured with a VaSera VS‐1000 (Fukuda Denshi, Tokyo, Japan) by the methods described previously . According to the manufacturer's recommendations, a CAVI <8 was considered normal; 8≤ CAVI <9 was considered borderline; and a CAVI ≥9 was considered abnormal .…”
Section: Methodsmentioning
confidence: 99%
“…13 The CAVI was measured with a VaSera VS-1000 (Fukuda Denshi, Tokyo, Japan) by the methods described previously. 12,14 According to the manufacturer's recommendations, a CAVI <8 was considered normal; 8≤ CAVI <9 was considered borderline; and a CAVI ≥9 was considered abnormal. 15 Patients with a CAVI ≥9 have been reported to have significantly higher mean and maximum intima-media thicknesses.…”
Section: Evaluation Of the Severity Of Atherosclerosismentioning
confidence: 99%